Effect of Thai ‘koi-hoi’ food flavoring on the viability and infectivity of the third-stage larvae of Angiostrongylus cantonensis (Nematoda: Angiostrongylidae) - Eamsobhana, P.; Yoolek, A.; Yong, Hoi Sen (Elsevier, 2010)
The effect of the food flavoring of ‘koi-hoi’, a popular Thai snail dish, on the viability and infectivity of Angiostrongylus (=Parastrongylus) cantonensis third-stage larvae was assessed in a mouse model. Groups of 50 each of actively moving, non-motile coiled, and extended larvae were obtained from experimentally infected snail meat, after one-hour exposure to standard ‘koi-hoi’ flavoring. These larvae and groups of 50 unexposed moving larvae (control) were individually fed to each group of three experimental BALB/c mice. The effect on Angiostrongylus worm burden was measured after 3 weeks of infection. Infectivity of the motile larvae after exposure to ‘koi-hoi’ food flavoring was 38 ± 5.29%. This was highly significantly lower than the infectivity (62 ± 7.21%) of the control (unexposed) third-stage larvae (χ2 = 17.28, P < 0.001). In the non-motile larvae resulting from exposure to the food flavoring, no adult worm was recovered from the extended larvae, indicating that they were no longer alive and unable to cause infection. A small proportion (3.33 ± 2.31%) of the coiled larvae developed into young adult worms, indicating that mobility alone is not a definitive indicator of viability. The present study confirms that the food flavoring components of ‘koi-hoi’ dish adversely affect the viability and infectivity of A. cantonensis larvae. Exposure of the third-stage larvae to ‘koi-hoi’ food flavoring resulted in decreased viability and eventually death. Prolonged treatment with food flavoring to inactivate/immobilize and then kill the infective, third-stage larvae of A. cantonensis in snail meat prior to consumption may be one of the possible economical means of reducing human infection.